Prevalence of Moraxella ovis infection in goats under the Ladang Angkat Programme of University Veterinary Hospital, Universiti Putra Malaysia - Gopi Naidu, Nagachandra Rao (2015)
Infectious keratoconjunctivitis or pink eye disease is recognized as one of the common diseases affecting the small ruminant industry as well as an important factor affecting production in this industry. The purpose of this study is to know the prevalence of Moraxella ovis infection in goats, the economic impact of pink eye disease and the role of flies as a vector of Moraxella ovis in the goat farms under the Ladang Angkat Program of UVH, UPM. 60 goats were selected randomly from 4 farms (15 goats per farm) and subconjunctival swab samples were taken from the animals. At the same time, a fly trap was set and a questionnaire was posed to the owner regarding the status of pink eye disease in their farm. Both the subconjuctival swabs and the fly samples were cultured on blood agar and the colonies were screened using Gram staining to isolate the most likely colonies. The pure isolates were then subjected for conventional Polymerase Chain Reaction (PCR) to detect for Moraxella ovis. From the 60 goat samples, 18 samples (30.00%) were positive for Moraxella ovis with Farm B had the highest prevalence where 6 goats were positive out of 15 (40.00%) and Farm C had the lowest prevalence where only 3 goats were positive(20.00%) for Moraxella ovis. Meanwhile, none of the fly samples were positive for Moraxella ovis. The questionnaire revealed that 3 out of 4 farmers (75.00%) opted that pink eye disease is a problem in the farm but it is not a priority or important disease in the farm. The mean percentage of animals affected annually was 16.50% according to the farmers with Farm C had the highest percentage of 50.00% and Farm D had the lowest of 2.00%. The mean percentage of goats that showed emaciation following clinical signs of pink eye disease were 7.25% with Farm C had the highest percentage of 20.00% and Farm D had the lowest percentage of 1%. For treatment, 3 out of 4 farms (75.00%) only used eye ointment or spray for treatment while the other farm opted for systemic antibiotic in addition to the eye ointment or spray. Therefore, we have concluded that the prevalence of Moraxella ovis infection among the goats in farms under the Ladang Angkat Program of UVH, UPM is 30.00% and the mean annual infection of pink eye is about 16.50% with 7.25% showing significant emaciation following the manifestation of clinical signs.